Multivalent Aptamer‐Functionalized Single‐Strand RNA Origami as Effective, Target‐Specific Anticoagulants with Corresponding Reversal Agents. Issue 11 (21st April 2021) - Krissanaprasit, Abhichart; Key, Carson M.; Froehlich, Kristen; Pontula, Sahil; Mihalko, Emily; Dupont, Daniel M.; Andersen, Ebbe S.; Kjems, Jørgen; Brown, Ashley C.; LaBean, Thomas H.
Abstract: Anticoagulants are commonly utilized during surgeries and to treat thrombotic diseases like stroke and deep vein thrombosis. However, conventional anticoagulants have serious side‐effects, narrow therapeutic windows, and lack safe reversal agents (antidotes). Here, an alternative RNA origami displaying RNA aptamers as target‐specific anticoagulant is described. Improved design and construction techniques for self‐folding, single‐molecule RNA origami as a platform for displaying pre‐selected RNA aptamers with precise orientational and spatial control are reported. Nuclease resistance is added using 2′‐fluoro‐modified pyrimidines during in vitro transcription. When four aptamers are displayed on the RNA origami platform, the measured thrombin inhibition and anticoagulation activity is higher than observed for free aptamers, ssRNA‐linked RNA aptamers, and RNA origami displaying fewer aptamers. Importantly, thrombin inhibition is immediately switched off by addition of specific reversal agents. Results for single‐stranded DNA (ssDNA) and single‐stranded peptide nucleic acid (PNA) antidotes show restoration of 63% and 95% coagulation activity, respectively. To demonstrate potential for practical, long‐term storage for clinical use, RNA origami is freeze‐dried, and stored at room temperature. Freshly produced and freeze‐dried RNA show identical levels of activity in coagulation assays. Compared to current commercial intravenous anticoagulants, RNA origami‐based molecules show promise as safer alternatives with rapid activity switching for future therapeutic applications. Abstract : Improved RNA origami‐based anticoagulants are described, where thrombin‐binding aptamers are displayed on origami platforms and positioned for optimal spacing and orientation to maximize anticoagulant activity. Complementary nucleic acid reversal agents (antidotes) are shown to rapidly restore coagulation activity by inhibiting aptamer action. Freshly transcribed as well as freeze dried RNA samples show equally high efficacy.